(untitled) (INNOVATIVE ECONOMY, 2024)
Shulyk V.O. FISCAL POLICY CHANGES: OPPORTUNITIES AND RISKS FOR REGIONAL DEVELOPMENT Purpose. Evaluation of recent fiscal initiatives in the context of ensuring a reasonable balance between the volume and sources of tax revenues, the distribution of such resources, and the maintenance of a necessary level of business activity in times of war or post-war recovery. The study also involves an analysis of the state and availability of alternative funding instruments for budgetary expenditures and an assessment of the impact of fiscal initiatives on taxpayers. Methodology of research. The setting goal was achieved through the use of such methods analysis of scientific literature, normative documents to study the situation with the payment and administration of taxes; comparison of revenues to the budgets by components and dynamics, sources of financing budget deficits; systematization and generalization of the literature on the possibility and risks of using certain proposed fiscal instruments. The study is based on the analysis of data from various sources, including budget indicators (income and expenditures by components, sources of financing the budget deficit), fiscal statistics (tax rates, number of taxpayers by types of taxes, tax debt), socio-economic indicators (demography, level destruction caused by military actions) and the legal framework. Findings. The article assesses the vulnerability of local budgets in the context of their own revenue sources during wartime conditions and the expected changes in fiscal policy have done. Key fiscal initiatives since the onset of the widespread Russian invasion are analysed, identifying limitations with the greatest impact on the formation of the resource base of local budgets. The study also explores opportunities for financing regional development projects through budgetary funds and analyses the existing fiscal model. Originality. The article introduces a new approach to examining the relationship between fiscal policy and regional development, taking into account contemporary trends and economic conditions. It elucidates the connection between fiscal initiatives and factors influencing economic development during conflict or recovery. Practical value. The proposed research results enable the evaluation of key risks and the adaptation of interaction models between fiscal entities to the challenges of the present and future. Also, and the relationship between fiscal initiatives and factors that determine economic development in conflict or recovery conditions is also explained. The research can be used by scientists to build models of minimizing losses for budgets and preventing losses of the local economy when forming fiscal policy in terms of the tax base, tax rates and powers. Key words: fiscal policy, taxes, government budget, local budgets, regional development, tax revenues, taxpayers.